How do we become better people for the environment? : An appeal to 'green' virtues - Nur Khairah Mohd Samion (Nanyang Technological University, 2020)
Climate change has become the most significant debate in the 21st century. Often dubbed as the public policy from hell; scientists, politicians, and intellectuals are locked in a constant disagreement. It seems to have become a problem with an impossible solution. The climate crisis remains a cause of concern on a societal level because are constantly bombarded by news and images of weather-related natural disasters that are linked to climate change. Why are these apocalyptic-like situations still not enough to propel us to make better decisions when it comes to the environment? It remains a complex moral issue that needs to be investigated but the scope of this thesis paper concerns the moral responsibility that we have with regards to human-induced climate change. I argue that an adoption of ‘green’ virtues and changed behavior is crucial for a collective and unified global climate action. This approach would also be helpful in solving the economic-environmental dilemmas that interweave with the climate crisis. Solving it requires substantial effort from all members of the international community and a unified global climate action that begins with a change of everyday behavior. The practice of ‘green’ virtues is the best step forward.